Ethnogenetic racial patterns of Tabloncillo and Tuxpeño maize, as mechanisms of conservation of native germplasm - Vidal-Martínez, Víctor Antonio; Álvarez-Bravo, Arturo; Coutiño-Estrada, Bulmaro; Ruiz-Corral, José Ariel; Ramírez-Díaz, José Luis; Sánchez-González, José de Jesús (Revista Mexicana de Ciencias Agrícolas, 2018)
The diversity of the native maizes represented by the presence of primary races per se, genetic mixtures among them, the plurality of agroecosystems where they are cultivated and the interrelations between them; encourage the presence of ethnogenetic or varietal patterns. The presence of native maize in the State of Nayarit can now be considered broad, since they are found in all the municipalities. The objective of the present work was to know and highlight the importance of the Tabloncillo and Tuxpeño Races as ethnogenetic racial patterns determining the genetic conservation of the native maize of Nayarit. From 2008 to 2012 there were 166 collections, which were agronomically characterized and determined their racial classification. Plant variables (cob and grain) and environment based on their georeferencing were considered. The characteristics of length of cob, grain per row, width and length of grain allowed phenotypically identify the ethnogenetic pattern of Tabloncillo, and the characteristics of cob diameter, number of rows, grain thickness and volume of grain to Tuxpeño. The environmental variables allowed to corroborate the distribution of both ethnogenetic corridors and the location of their respective ecological niches.